Asylum and the Evolution of International Interest: A Study of Legal Concepts and International Disparities - Amal Madi Al-Subaie (International Journal of Law Research and Studies, 2025)
This research addresses the concept of asylum as one of the most pressing legal and humanitarian issues of our time. It explores the linguistic, legal, and legislative origins of the term “refugee,” analyzing definitions under international and regional treaties, and clarifying the defining criteria of refugee status while distinguishing it from similar categories. The study also reviews the various types of asylum and the causes behind its emergence, providing a historical overview of the development of international protection for refugees from the early 20th century to the present day. This introductory framework aims to establish a clear understanding of the foundational concepts of asylum and to shed light on the legal and humanitarian dilemmas facing this growing population worldwide.
Keywords: Asylum; Refugees; International Protection; Human Rights; International Law; Types of asylums; Refugee conventions